AN OBSERVATIONAL STUDY OF EFFECT OF LABOUR INDUCTION ON MECONIUM ASPIRATION AND FOETAL OUTCOME - GUPTA, RITU; TRIVEDI, SWATI; GUPTA, AYUSHI (International Journal of Current Pharmaceutical Research, 2023)
Objective: Labor induction is a widely used procedure to initiate artificial uterine contractions, but its impact on meconium aspiration and fetal outcome needs further investigation, as meconium aspiration syndrome (MAS) poses significant risks to the newborn, including respiratory distress and other complications. Methods: This prospective observational study evaluates labor induction and evaluate the occurrence of meconium aspiration and overall fetal outcomes. Data from a tertiary care hospital were analyzed, including mode of induction, gestational age, Bishop score, meconium-stained amniotic fluid, Apgar scores, NICU admissions, and other relevant parameters. Statistical analysis was conducted to identify significant associations. Results: This observational study aimed to explore the relationship between labor induction and meconium aspiration, as well as their impact on fetal well-being. Data analysis identified correlations between labor induction techniques, meconium-stained amniotic fluid, and neonatal outcomes, offering valuable insights for clinical decision-making and optimizing fetal outcomes. Conclusion: The impact of labor induction on meconium aspiration and fetal outcomes was investigated in this study, providing valuable insights for healthcare professionals and contributing to the improvement of safety guidelines for obstetric care.